2015
DOI: 10.3174/ajnr.a4421
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Differences between Intra-Arterial Iso- and Low-Osmolality Iodinated Radiographic Contrast Media in the Interventional Management of Stroke III Trial

Abstract: BACKGROUND AND PURPOSE:Intracarotid arterial infusion of nonionic, low-osmolal iohexol contrast medium has been associated with increased intracranial hemorrhage in a rat middle cerebral artery occlusion model compared with saline infusion. Iso-osmolal iodixanol (290 mOsm/kg H 2 O) infusion demonstrated smaller infarcts and less intracranial hemorrhage compared with low-osmolal iopamidol and saline. No studies comparing iodinated radiographic contrast media in human stroke have been performed, to our knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…7 In some studies, the incidence of CIN in patients receiving non-ionic iso-osmolar CM was lower than that of iso-osmolar CM, 11 although a randomized study showed that iodixanol provides a less cytotoxic endothelial effect that protects renal function. 12 A meta-analysis by Biondi-Zoccai et al showed that iodixanol, iomeprol, iopamidol, and ioversol are CM with a similar renal safety profile and can therefore be routinely used for interventional diagnosis and imaging. However, iohexol and ioxaglate would be contraindicated.…”
Section: Discussionmentioning
confidence: 99%
“…7 In some studies, the incidence of CIN in patients receiving non-ionic iso-osmolar CM was lower than that of iso-osmolar CM, 11 although a randomized study showed that iodixanol provides a less cytotoxic endothelial effect that protects renal function. 12 A meta-analysis by Biondi-Zoccai et al showed that iodixanol, iomeprol, iopamidol, and ioversol are CM with a similar renal safety profile and can therefore be routinely used for interventional diagnosis and imaging. However, iohexol and ioxaglate would be contraindicated.…”
Section: Discussionmentioning
confidence: 99%
“…Class II signal (T2 hypointensity with no GRE hypointensity), supporting IRCM deposition rather than hemorrhagic changes, was more common in the IRCM group than with saline. Although many potential explanations for observed differences in HT between IRCM subgroups have been previously entertained (eg, osmolality, coagulative, blood–brain barrier disruption, hydrodynamic/viscosity,20–22 and/or molecular size differences),10 23 24 the influence of IRCM use on the amount and type of HT with reperfusion remains incompletely understood 17 25–27. The findings here suggest less HT in the iodixanol subgroup, possibly related to larger molecular size and less leakage across the blood–brain barrier, or may also reflect a hydrodynamic effect of its viscous macromolecular properties.…”
Section: Discussionmentioning
confidence: 99%
“…2 Various issues raised in post hoc analysis should be of value to future investigators planning their own studies. [3][4][5] To the correspondents' specific concerns regarding poor recanalization, the Interventional Management of Stroke (IMS) III study showed a recanalization rate of 78.3% for M2 occlusion, with 72.3% modified TICI 2-3 and approximately 40% modified TICI 2b-3 reperfusion rate. However, in IMS III, revascularization (recanalization and reperfusion) had no interobserver agreement for distinction between modified TICI 2-3 and 2b-3 reperfusion versus outcome and did not correlate to good clinical outcome for M2 occlusion.…”
mentioning
confidence: 99%